Implementasi Teori Konsep Ida Jean Orlando Dalam Pemberian Asuhan Keperawatan Pada Pasien Fraktur Humerus - Fenny Maryani; Irna Nursanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Fractures can occur in all bones, one of which is a humerus fracture. Humerus fracture is a fracture of the longest and largest bone of the superior extremity caused by direct or indirect impact or trauma. Ida Jean Orlando, is a first generation Irish-American who was born on August 12, 1926 in New Jersey. Ida Jean Orlando's concept model is known as The Discipline and Teaching of Nursing Process: An Evaluative Study”. Ida Jean Orlando first published her theory in